(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
This article is an ecclesionomatic study in the framework of linguistics landscape discussing the categories and language of church names in Kupang city, Indonesia. Data were obtained from signboards in Kupang City through photographic techniques in September 2021. The results showed that the names of churches in the city of Kupang were divided into 7 categories, namely biblical terms, names of people, names of places, churches as residences, topographic, names of plants and animals. From the language used, there are 7 languages ​​in the church name, namely Indonesian, Hebrew, Greek, Latin, English, Aramaic, and Dawan languages. The use of a foreign language other than English in church names is not related to literacy or congregational culture but has a symbolic function that contains values ​​and ideology because these names are taken from the Bible and have meaning. Meanwhile, English follows developments and shows the internationality of the church. In addition, the Dawan language is the only language used in the name of the church to show the locality of culture and as a marker of identity in the area.